A system science methodology develops a new composite highly predictable index of magnetospheric activity for the community: the whole-Earth index E(1) - Borovsky, Joseph E.; Lao, Christian J. (Frontiers in Astronomy and Space Sciences, 2023)
For community use, a new composite whole-Earth index E(1) and its matching composite solar-wind driving function S(1) are derived. A system-science methodology is used based on a time-dependent magnetospheric state vector and a solar-wind state vector, with canonical correlation analysis (CCA) used to reduce the two state vectors to the two time-dependent scalars E(1)(t) and S(1)(t). The whole-Earth index E(1) is based on a diversity of measures via six diverse geomagnetic indices that will be readily available into the future: SML, SMU, Ap60, SYMH, ASYM, and PCC. The CCA-derived composite index has several advantages. (1) The new “canonical” geomagnetic index E(1) will provide a more-powerful description of magnetospheric activity: a description of the collective behavior of the magnetosphere-ionosphere system. (2) The new index E(1) is much-more-accurately predictable from upstream solar-wind measurements at Earth. (3) Indications are that the new canonical geomagnetic index E(1) will be accurately predictable even when as-yet-unseen extreme solar-wind conditions occur. The composite solar-wind driver S(1) can also be used as a universal driver function for individual geomagnetic indices or for magnetospheric particle populations. To familiarize the use of the new index E(1), its behavior is examined in the different phases of the solar cycle, in different types of solar-wind plasma, during high-speed-stream-driven storms, during CME-sheath-driven storms, and during superstorms. It is suggested that the definition of storms are the times when E(1) > 1.